Odpowiedź :
[tex]d) \ 1\frac{7}{8}\cdot\frac{3}{150}\cdot4\frac{4}{5} =\frac{15}{8}\cdot\frac{1}{50}\cdot\frac{24}{5} =\frac{15}{5}\cdot\frac{24}{8}\cdot\frac{1}{50} = 3\cdot3\cdot\frac{1}{50} = \frac{9}{50}\\\\\\e) \ 6-1\frac{1}{2}\cdot\frac{2}{3}=6-\frac{3}{2}\cdot\frac{2}{3}=6-1 = 5\\\\\\f) \ (2\frac{5}{8}-1\frac{1}{6}):2\frac{1}{2} = (\frac{21}{8}-\frac{7}{6}):\frac{5}{2} = (\frac{63}{24}-\frac{28}{24})\cdot\frac{2}{5} = \frac{35}{24}\cdot\frac{2}{5} = \frac{7}{12}[/tex]
-------------------------------------------------------------------------------------
[tex]g) \ (-3\frac{4}{5}-\frac{1}{5})\cdot(-3,7+1\frac{2}{5}) = (-3\frac{5}{5})\cdot(-\frac{37}{10}+\frac{7}{5}) = -4\cdot(-\frac{37}{10}+\frac{14}{10}) = -4\cdot(-\frac{23}{10}) = \\\\=\frac{46}{5} =}9\frac{1}{5} = 9,2[/tex]